Climate Change Assessment in Brazil: Utilizing the Köppen-Geiger (1936) Climate Classification - de Lima, Rafael Fausto [UNESP]; de Oliveira Aparecido, Lucas Eduardo; Torsoni, Guilherme Botega; de Souza Rolim, Glauco [UNESP] (FapUNIFESP (SciELO), 2023)
Analyses and climate forecasts indicate significant changes in climate elements, particularly the global mean temperature, and variations in rainfall patterns, which can have profound effects on ecosystems and agriculture. This study aims to assess the impacts of climate change on the Brazilian territory using the Köppen-Geiger (1936) climate classification. Climate data were analyzed at 4,942 locations, encompassing municipalities in Brazil from 1989 to 2019. These data were obtained from the NASA/POWER platform and complemented with monthly temperature and rainfall projections from the BCC-CSM1-1 model, part of the CMIP5 (Coupled Model Intercomparison Project Phase 5), under four emission scenarios (RCP 2.6, RCP 4.5, RCP 6.0, and RCP 8.5) for the periods 2041-2060 and 2061-2080. The findings reveal a temperature increase across all scenarios, with RCP 8.5 indicating the most significant rise, reaching 4.30 and 5.42 °C for the periods 2041-2060 and 2061-2080, respectively. Additionally, the least rainy month of the year exhibits precipitation values exceeding 60 mm, leading to the dominance of the tropical climate typology “A” in 82.94% of the current climate assessment. In contrast, under climate change scenarios, reductions in areas with typical temperate cli mate “C” and expansions in arid climate “B” and tropical climate classes were observed compared to the present climate pattern. Notably, the BSh class has a prevalence of 6.09% and 8.16% for the periods 2041-2060 and 2061-2080, respectively. The observed climate changes signal potential challenges for the preservation of species in Brazil, as higher temperatures may hinder their adaptability to drier and warmer conditions. As a result, careful measures and strategies are needed to address the implications of these changes in the coming decades.
Keywords: arid climate; CMIP5 projections; emission scenarios; global mean temperature